Unveiling promotion effects of Ce doping in La0.6Ca0.4Co0.2Fe0.8O3-δ as an efficient cathode for solid oxide fuel cells - He, S.; Li, Z.; Hu, X.; Li, Q.; Song, X.; Wang, Y.; Zhang, X.; Zhong, H.; Tian, Y.; Jiang, San Ping (2025)
Perovskite La0.6Sr0.4Co0.2Fe0.8O3-δ (LSCF) is to date the most intensively studied high-performance cathode material for solid oxide fuel cells (SOFCs), but strontium segregation at elevated temperatures critically impairs the activity and longevity of LSCF cathode. By substituting Sr with Ca, i.e. La0.6Ca0.4Co0.2Fe0.8O3-δ (LCCF), the stability of the perovskite can be reinforced, however, at the cost of reduced catalytic activity. Herein, we adopt an effective A-site Ce doping strategy to modify the structure and chemistry of LCCF and therefore to boost its electrochemical performance, i.e. La0.6Ca0.4-xCexCo0.2Fe0.8O3-δ (Ce-LCCFx, x = 0.05–0.2). The results reveal that replacing Ca2+ with Ce4+ notably alters the oxygen vacancies concentration, Fe4+/Fe3+ and Co4+/Co3+ proportions in the perovskite. As a result, the thermal expansion coefficient of LCCF is drastically lowered to 12.6 × 10−6 K−1 upon x = 0.15 in Ce-LCCFx. Moreover, the single cell loaded with Ce-LCCF15 cathode demonstrates a superior maximum power density of 1.26 W cm−2 at 750 °C in H2. Interestingly, microstructure analysis suggests that abundant CeOx nanoparticles are exsolved in situ from the Ce-LCCF15 surfaces due to cathodic current polarization. The present study contributes to the understanding of the role of dopants in promoting the catalytic properties of cathode materials for SOFCs.